Upaya Peningkatan Pengetahuan Remaja terhadap Kesehatan Reproduksi melalui Pelatihan Life Skill Education - Ratu Matahari; Fitriana Putri Utami; Dedik Sulistiawan (Universitas Mathla'ul Anwar Banten, 2020)
THE EFFORTS TO INCREASE ADOLESCENT KNOWLEDGE OF REPRODUCTIVE HEALTH THROUGH LIFE SKILL EDUCATION TRAINING. The internet will make adolescent easier to access information needs and carry out productive activities based on technology; on the other hand it will be backfiring when used to access some things that are counterproductive. Life skill education training for adolescent reproductive health is an effort to improve adolescent skills in self-management in facing and solving reproductive health problems they faced. The method used is a theoretical approach and practice through case studies and role play. Reproductive health life skill education training can have an impact on increasing adolescent reproductive health knowledge even though it has little impact.The conclusion of the activity was life skill education training for adolescent reproductive health in the PIK-KRR ABC group in XYZ Village, Bantul District can increase teenage knowledge, although not significantly due to the small number of trainees. This is an evaluation of the service team to collaborate with other youth groups in providing reproductive health education.